INNOVATIONS IN THE USE OF ACIDIFIERS: MODERN SOLUTIONS FOR LIVESTOCK PRODUCTION AND INTELLECTUAL PROPERTY ASPECTS - I. Chernega; L. Fihurska; B. Iegorov; A. Makarynska; O. Tsiundyk (Zernovì Produkti ì Kombìkorma)
The article examines innovative approaches to the use of acidifiers in animal husbandry, their impact on animal productivity and health, as well as intellectual property aspects associated with the development and implementation of such solutions. The growing demand for animal products, in particular meat and eggs, leads to an increase in the number of animals and poultry and the need for effective solutions for their complete nutrition. This increases the demand for effective feed additives. The market for feed acidifiers is actively gaining momentum, as they meet modern requirements for efficient, safe and economical farming. Acidifiers help maintain an optimal pH level in the digestive system of animals, which contributes to better absorption of nutrients and reduces the risk of digestive disorders. They also stimulate the development of beneficial microflora in the gastrointestinal tract, which has a positive effect on the general condition of animals. In many countries, stricter restrictions on the use of antibiotics in livestock farming are being introduced due to concerns about bacterial resistance to drugs. Therefore, acidifiers are becoming an effective alternative to maintaining animal health without the use of antibiotics. In addition, acidifiers can increase the efficiency of feed processing, which allows you to reduce feed costs and increase the feed conversion ratio. This is important for farmers, as it allows achieving better results at lower costs. With the development of industrial animal husbandry, there is a need for more effective feeding methods, which makes feed acidifiers an important tool in maintaining animal health and productivity. The article examines the global and domestic market for acidifiers. A literature review of the results of the use of feed acidifiers in animal and poultry feeding by leading domestic scientists is presented. The results of tests are presented, which showed that the use of feed acidifier in feeding young pigs has a significant effect on biochemical blood parameters, meat quality and animal growth rate. Other data showed that adding acidifiers to the diet of broiler chickens contributed to an increase in survival, leads to feed savings while increasing productivity. The article also presents the main prospects, problems of using acidifiers in compound feed production and ways to solve them.